2006
DOI: 10.1038/sj.bjc.6603331
|View full text |Cite
|
Sign up to set email alerts
|

The multikinase inhibitor midostaurin (PKC412A) lacks activity in metastatic melanoma: a phase IIA clinical and biologic study

Abstract: Midostaurin (PKC412A), N-benzoyl-staurosporine, potently inhibits protein kinase C alpha (PKCa), VEGFR2, KIT, PDGFR and FLT3 tyrosine kinases. In mice, midostaurin slows growth and delays lung metastasis of melanoma cell lines. We aimed to test midostaurin's safety, efficacy and biologic activity in a Phase IIA clinical trial in patients with metastatic melanoma. Seventeen patients with advanced metastatic melanoma received midostaurin 75 mg p.o. t.i.d., unless toxicity or disease progression supervened. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 12 publications
0
32
0
1
Order By: Relevance
“…Likewise, another KIT inhibitor, PKC412, showed little activity in melanoma (12). However, Becker et al (36) observed in a recent editorial that their imatinib trial was underpowered to detect activity in the subtypes of melanomas most likely to harbor a KIT mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, another KIT inhibitor, PKC412, showed little activity in melanoma (12). However, Becker et al (36) observed in a recent editorial that their imatinib trial was underpowered to detect activity in the subtypes of melanomas most likely to harbor a KIT mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Midostaurin (34) was the first PKC inhibitor evaluated in clinical trials; however, it has failed to demonstrate significant activity in clinical trials to date (35). ISIS 3521, a phosphorothioate antisense oligonucleotide targeting the 3 0 -untranslated region of PKC-a mRNA (36,37), demonstrated anticancer activity in various types of cancers, including tumors refractory to conventional chemotherapy (38,39), but has so far failed to exert clinically significant efficacy when combined with chemotherapy against advanced lung cancer in phase III trials (40).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the BIM PKC412 is a PKC inhibitor, but it has also been identified as an FLT3 inhibitor (40) along with the compound CEP-701 (4). In a phase II trial of PKC412, plasma concentrations of the parent compound as high as 4 Amol/L have been reported (41). Interestingly, serum concentrations of metabolites of PKC412, also indolocarbazoles, have been reported to be as high as 22 Amol/L (41), thus suggesting that the metabolites might also act as inhibitors of ABCG2.…”
Section: Discussionmentioning
confidence: 99%